Pengaruh Manajemen Literasi Keuangan, Adopsi Teknologi, dan Keputusan Investasi Masyarakat Digital (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of digital financial services has increased public access to various technology-based investment instruments. However, the quality of investment decisions is determined not only by ease of access to technology, but also by an individual's ability to understand and manage financial information effectively. This study aims to analyze the influence of financial literacy management and technology adoption on investment decisions of Indonesians in the digital financial era. The study used a quantitative explanatory approach involving 385 digital financial service users selected through purposive sampling and simple quota sampling techniques. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression after meeting validity, reliability, and classical assumptions. The results showed that financial literacy management had a positive and significant effect on investment decisions (B = 0.351; t = 7.278; p < 0.001), as did technology adoption, which had a positive and significant effect (B = 0.456; t = 9.756; p < 0.001). Simultaneously, both variables significantly influenced investment decisions (F = 221.639; p < 0.001) with an R² value of 0.537. This finding indicates that improving financial literacy and optimal use of technology play a significant role in supporting more rational and quality investment decision-making.